Luis Santacruz: capstone - Luis, Santacruz, artist (Colorado State University. Libraries, 2021)
The artist's statement: I have forgotten the memories of my Mexican home. My family and I embarked on the journey to America when I was four. We were part of a Mexican diaspora, where violence, poverty, and corrupt politics would push us out, and the greener pastures of American capitalism would pull us in. During this transition, we had to leave everything - family pictures, furniture, heirlooms, and the very home that my father built for our family. We had to make it seem like we were only visiting the United States to avoid questioning by immigration agents. My Mexican identity and history stayed trapped in Mexico, caged by the politics that have defined our lives. This has caused a deep desire in myself to connect to my Mexican heritage and unravel the identity that has been suppressed by the idealization of the successful American. In the United States, I have always felt marginalized - "ni de aqui, ni de alla", (I am neither from here nor there). This idea of being an outsider has prompted me to shift my artwork to depict myself and my reality. I hope to infuse my work with the beauty and grace that I see in my identity and that of other immigrants - which is in stark contrast to what the media and politics have shaped us to be. My identity as an immigrant has given me limitations. I cannot visit family in Mexico or leave the country, I can't vote, and I cannot apply for citizenship. I am having to find part of my cultural identity through means of technology and the resources I have available to myself. I begin the paintings by looking at Mexican artists like Frida Kahlo, Nahum B. Zenil, and Jose Maria Valesco. I also look to classical artists like Diego Velasquez and contemporary artists like Njideka Akunyili Crosby, where a lot of my inspiration for subject matter and composition comes from. This results in the use of photo media to create my composition through layers that are reflective of different parts of my identity. I rely on old family photos to give me a glimpse and idea of life in Mexico. I also take photos myself to capture my family in the poses I feel are best for the composition. The plants and wildlife that surround my family are symbolic of the great virtues and positive attributes that my family has provided to our host country and as a reminder that we are a part of nature. I hope this work will make the viewer rethink what role immigrants have in shaping the American landscape.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting